PAKET PELATIHAN SELF TALK BAGI MAHASISWA YANG MENGALAMI COMMUNICATION APPREHENSION - Permatasari, Devi; Sari, Eva Kartika Wulan (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2024)
Communication motives that are not conveyed properly then individuals experience communication anxiety. Communication anxiety can occur when speaking in public or in new situations, and is different from before. Thus causing a person to experience anxiety. So self-talk training is needed for students who experience communication anxiety. The research model used in the development of the Self Talk training package to reduce communication anxiety for new students of the Faculty of Education, PGRI Kanjuruhan University Malang, uses the ADDIE research and development model. Research and development that has been carried out by researchers produces products in the form of this training package has a function as a medium in order to facilitate counselors to help students reduce anxiety in communicating with self-speech or self-talk. The results of the validity test of Guidance and Counseling experts, and learning media experts, on the training package developed by researchers have met the criteria for acceptance. This can be seen from the results of the assessment of experts with interrater agrrement model analysis. According to the expert assessment of Guidance and Counseling on the usability aspect, showing a value of 1 that is more than 0.8 then has high validity, or in other words very good. In the feasibility aspect, it shows a value of 0.75 which means between 0.4 – 0.8 then it has moderate validity, or in other words enough. In the aspect of accuracy, it shows a value of 0.6 which means between 0.4 – 0.8 then it has moderate validity, or in other words enough. While the assessment of learning media experts on the aspect of propriety / attractiveness shows a value of 1 which means more than 0.8 then it has high validity, or in other words very good. The test results of prospective users on the training package developed by researchers have met the criteria for acceptability. This can be seen from the assessment results of prospective users with interrater agrrement model analysis. According to the assessment of prospective users / counselors on the usability aspect, showing a value of 1 which means more than 0.8, then it has high validity, or in other words very good. In the feasibility aspect, showing a value of 1 which means above 0.8, it has high validity, or in other words very good. In the aspect of accuracy, showing a value of 1 which means more than 0.8, it has high validity, or in other words very good. Suggestions for future researchers, this research is still in the development stage, has not been implemented, therefore the suggestion for the next researcher is to test the effectiveness of the guide with a pure experimental design, to use it for students to help reduce communication anxiety, in order to find out whether or not this training package is effective if applied to students